INTERNATIONAL ECONOMIC INTEGRATION AS A FACTOR OF ECONOMIC DEVELOPMENT - Roshka, Petru (SWorldJournal, 2025)
Various aspects of the international division of labor are studied in the article; essence, premises and objectives of integration, forms, stages of development and role of this process in the economic growth of the Republic of Moldova. A general characte